Dynamic optimization in the coordination and control of autonomous underwater vehicles - João Borges de Sousa (2002)
The coordination and control problems arising in team composition and tasking of autonomous underwater vehicles are discussed in the framework of dynamic optimization. Team composition and tasking are specified in terms of sets and relations among the elements of these sets. Results from dynamic optimization and non-smooth analysis are used to show that these coordination and control problems can be phrased in terms of concepts such as invariance, solvability, monotonicity, and switchings among value functions.